2003
DOI: 10.1038/sj.onc.1207110
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic cues from the extracellular matrix: regulators of angiogenesis

Abstract: A variety of factors cooperate to regulate neovessel formation and persistence. Proangiogenic growth factors have remained an area of intense interest due to their capacity to promote endothelial cell (EC) proliferation and to initiate the angiogenic program. These growth factors are associated with increased cell survival, yet paradoxically, angiogenic ECs are more susceptible to apoptosis than quiescent ECs. Survival is regulated by cooperation between growth factor receptors and integrins, which are in turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 75 publications
4
96
0
1
Order By: Relevance
“…49 However, the receptor switches to proapoptotic activity when triggered by ligands not anchored to the extracellular matrix. 50 This occurs during detachment of therapeutic EPCs from their culture matrix and during homing to the tumor. 51 EPCs derived from blood express high levels of the antioxidative enzymes MnSOD, catalase and glutathione peroxidase leading to decreased oxidative stress-induced apoptosis.…”
Section: Antiapoptotic Default Mode Of Epcsmentioning
confidence: 99%
“…49 However, the receptor switches to proapoptotic activity when triggered by ligands not anchored to the extracellular matrix. 50 This occurs during detachment of therapeutic EPCs from their culture matrix and during homing to the tumor. 51 EPCs derived from blood express high levels of the antioxidative enzymes MnSOD, catalase and glutathione peroxidase leading to decreased oxidative stress-induced apoptosis.…”
Section: Antiapoptotic Default Mode Of Epcsmentioning
confidence: 99%
“…In particular, proteolytic cleavage of pre-existing matrix proteins can alter the integrity (and physical rigidity) of the local microenvironment and provide soluble ECM fragments which can antagonize integrin binding to substrate ECM. 108 When one considers the capacity of integrin-mediated adhesion to modulate both apoptotic and growth factor signaling, the sequential alterations to the ECM that occur during tissue remodeling provide an elegant mechanism to attune the responses of individual cells based on the status of a particular cell's immediate microenvironment.…”
Section: Physiological Roles For Cellular 'Dependence' On the Ecmmentioning
confidence: 99%
“…8 10.1074/mcp.M110.005264 -7 the retina (42). On the other hand, casepase-8, which plays a role in p53-induced apoptosis, was activated by unligated integrin ␣ v ␤ 3 followed by apoptosis (40).…”
Section: Pharmacoproteomic Analysis Of P11mentioning
confidence: 99%
“…It was reported that bFGF-induced ERK activation was required for vascular angiogenesis (41). Integrin ␣ v ␤ 3 antagonist inhibited the ERK signaling lead to endothelial cell apoptosis and blockade of angiogenesis (42). Antagonists of integrin ␣ v ␤ 3 disrupt bFGF-induced neovascularization via suppressing c-Raf-ERK activation (43).…”
Section: Pharmacoproteomic Analysis Of P11mentioning
confidence: 99%